Influence of Shape Design of MEMS (Micro-Cantilever Based Sensor) on High-Sensitivity - Ibtissam Mahdi Shihab (Engineering and Technology Journal, 2012)
In this paper, a novel analysis was carried out on the biosensor microcantilevers in order to increase the sensitivity of a micro- cantilever based biosensor piezoresistive. Holes were made and compared with the basic rectangular (R), triangular (T), and step(S) profile cantilever. Effect of changing the micro-cantilevers profile and its cross-section shape was investigated. A finite element ANSYS was used to analyze these models. The micro-cantilevers are made of silicon with elastic modulus 130Gpa and poisson’s ratio 0.28. Several cases were studied by making one, two and three holes in each biosensor piezoresistive micro-cantilevers (rectangular (R), triangular (T), and step(S) profile cantilever). Results showed that triangular micro-cantilever with two holes (T22) has the better sensitivity, also showed T12 respectively 61.7% and 65% higher sensitivity than R12, S12.